Neurotensin Branched Peptide as a Tumor-Targeting Agent for Human Bladder Cancer. (23rd April 2015) - Brunetti, Jlenia; Falciani, Chiara; Lelli, Barbara; Minervini, Andrea; Ravenni, Niccolò; Depau, Lorenzo; Siena, Giampaolo; Tenori, Eleonora; Menichetti, Stefano; Pini, Alessandro; Carini, Marco; Bracci, Luisa
Abstract : Despite recent advances in multimodal therapy, bladder cancer still ranks ninth in worldwide cancer incidence. New molecules which might improve early diagnosis and therapeutic efficiency for tumors of such high epidemiological impact therefore have very high priority. In the present study, the tetrabranched neurotensin peptide NT4 was conjugated with functional units for cancer-cell imaging or therapy and was tested on bladder cancer cell lines and specimens from bladder cancer surgical resections, in order to evaluate its potential for targeted personalized therapy of bladder cancer. Fluorophore-conjugated NT4 distinguished healthy and cancer tissues with good statistical significance P < 0.05 . NT4 conjugated to methotrexate or gemcitabine was cytotoxic for human bladder cancer cell lines at micromolar concentrations. Their selectivity for bladder cancer tissue and capacity to carry tracers or drugs make NT4 peptides candidate tumor targeting agents for tracing cancer cells and for personalized therapy of human bladder cancer.